2020
DOI: 10.37506/ijfmt.v14i3.10490
|View full text |Cite
|
Sign up to set email alerts
|

A Chronic Toxicity Study of Oral Administration of Collagen-?® Supplement using Pregnant Rabbits

Abstract: Since collagen derived products are highly used in food supplements due to its bioactive properties by influencing cellular and tissue health, flexibility with high effect of repairing and adaptation. It is necessary to carry out safety requirement of an oral chronic toxicity assessment. This study investigated the adverse effect of long term oral administration of collagen-® in pregnant rabbits. We have conducted a thirty days randomized controlled trial in pregnant rabbits. Rabbits were randomized into two g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…In this study, we reported decreased in liver and kidneys weights, these may be due to its acts as anti-obesity by it regulation metabolism of lipids and proteins and also may be suggested it effects on appetite centers in the brain (20). These changes in the liver, and kidneys weights agreement with that reported by Kudayeret al (9) who noted that used 1 ml of CH-α® supplementation for pregnant rabbits for 30 days have adverse effect on liver and kidney weights and its functions and also signed to changes negatively in body weight and BW gain. The histological changes recorded in figures of liverand kidneys related to the changes in body, organs weights and BW changes and similar to that reported by Kudayeret al (9) that notes increase in elasticity of muscles but decrease in muscle mass.…”
supporting
confidence: 91%
See 4 more Smart Citations
“…In this study, we reported decreased in liver and kidneys weights, these may be due to its acts as anti-obesity by it regulation metabolism of lipids and proteins and also may be suggested it effects on appetite centers in the brain (20). These changes in the liver, and kidneys weights agreement with that reported by Kudayeret al (9) who noted that used 1 ml of CH-α® supplementation for pregnant rabbits for 30 days have adverse effect on liver and kidney weights and its functions and also signed to changes negatively in body weight and BW gain. The histological changes recorded in figures of liverand kidneys related to the changes in body, organs weights and BW changes and similar to that reported by Kudayeret al (9) that notes increase in elasticity of muscles but decrease in muscle mass.…”
supporting
confidence: 91%
“…These changes in the liver, and kidneys weights agreement with that reported by Kudayeret al (9) who noted that used 1 ml of CH-α® supplementation for pregnant rabbits for 30 days have adverse effect on liver and kidney weights and its functions and also signed to changes negatively in body weight and BW gain. The histological changes recorded in figures of liverand kidneys related to the changes in body, organs weights and BW changes and similar to that reported by Kudayeret al (9) that notes increase in elasticity of muscles but decrease in muscle mass. Like other types of animal protein, collagen contains a type of amino acid called hydroxyproline (21).…”
supporting
confidence: 90%
See 3 more Smart Citations